PARTICLE PHYSICS IN HIGH SCHOOL: A LOOK AT TEACHING MATERIALS - do Nascimento, Girleide Araujo; Sampaio, Jarbas Cordeiro (Seven Editora, 2025)
Physics is a science that permeates everyday life. With the technological growth and the greater availability of resources resulting from this advance, there is a need to develop work related to the insertion of the study of modern and contemporary Physics in high school. These contents aim to promote the understanding of the universe, allowing the student to perceive and understand the natural and technological phenomena around them.The study of particle physics provides a view of the microscopic universe. In the quest to understand nature, this science contributes significantly by emphasizing the possible gaps that exist in classical physics. Particle physics is directly linked to atomic models, which are addressed in the disciplines of Physics and Chemistry. The knowledge acquired through this study can be applied in several areas, such as computing, nanotechnology, nanoscience, medicine and biotechnology.Several factors can contribute to the absence of an approach to these contents in high school, such as the lack of themes in the didactic and methodological materials and the lack of curricular updating (MOREIRA, 2009; SEE; PIETROCOLA, 2006). Therefore, it is important to analyze the approach of Particle Physics, which can help teachers and students in advancing the understanding of nature.The contents of Modern Physics and Particle Physics are often covered in the 3rd year textbooks, being the last to be presented. For this reason, they may not be seen due to time constraints (NETO, 2020), which makes it necessary to renew their curricula (SIQUEIRA; PIETROCOLA, 2006). It is essential to analyze the importance of the study of particle physics in high school, as well as the way it is approached, reviewing the didactic materials available for the insertion of this content (TEIXEIRA; GODOY, 2021).One of the ways to make particle physics classes more interactive and fun for students is through the use of didactic games (SOUZA et. al., 2019; SILVA, 2019; OLIVEIRA and SIQUEIRA, 2018). This proposes ways of inserting available teaching materials, which can be applied in conjunction with the teaching of classical Physics, as in the content of electrostatics. Given the constant evolution of studies on the phenomena of nature, it is essential to understand physics in a contemporary context. This work aims to analyze the approach of particle physics in the didactic materials used in high school, evaluating its effectiveness and adequacy for student learning.For this, a review of the existing literature on particle physics and its relevance in the high school curriculum will be made. In addition, educational games that address particle physics are analyzed, evaluating their potential as teaching tools.With these analyses, it is intended to identify gaps in teaching materials and propose recommendations to improve the inclusion of particle physics in high school. This approach aims not only to enrich students' knowledge but also to better prepare students for the contemporary challenges of science.The next section deals with the theoretical framework on Particle Physics, its approach in high school and its resources.DOI: https://doi.org/10.56238/sevened2025.018-014